2017
DOI: 10.1016/j.jdent.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cariogram for root caries prediction

Abstract: Identification of a caries risk assessment tool which could reliably select high-risk individuals for root caries prevention strategies would maximise the cost effectiveness of professionally delivered prevention measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
(32 reference statements)
1
15
1
Order By: Relevance
“…Assessing caries risk is an essential element in the planning of preventive and therapeutic strategies [13]. The Cariogram model proposed by Petersson et al in 1996 has higher accuracy in predicting the trend of caries development, and is an ideal multi-factor caries risk assessment model [13][14][15]. It graphically displays an individual's caries risk pro le, simultaneously taking into account the interaction between different causative factors and parameters of caries [16].…”
Section: Introductionmentioning
confidence: 99%
“…Assessing caries risk is an essential element in the planning of preventive and therapeutic strategies [13]. The Cariogram model proposed by Petersson et al in 1996 has higher accuracy in predicting the trend of caries development, and is an ideal multi-factor caries risk assessment model [13][14][15]. It graphically displays an individual's caries risk pro le, simultaneously taking into account the interaction between different causative factors and parameters of caries [16].…”
Section: Introductionmentioning
confidence: 99%
“…23 Dental caries in particular remains a problem for this age group with a high prevalence of coronal and root surface caries found amongst old-age populations. 24,25 In the 1998 UK Adult Dental Health Survey, the proportion of adults with 18 or more sound and unrestored teeth was only 5% among those aged 55 years and over. The 2009 UK Adult Dental Health Survey indicated that this figure had improved but still remained at only 13%.…”
Section: The Oral Health Of Older Adultsmentioning
confidence: 99%
“…23 More recently, in a prospective randomised study of root caries in elderly patients, Hayes et al showed that patients categorised as highest level of risk by the Cariogram at baseline did indeed have the highest root caries incidence 24 months later. 24 Care strategies can be tailored more accurately when level of risk is systematically and correctly identified.…”
Section: Ris K a Ss E Ss Mentmentioning
confidence: 99%